A feature-based framework for semantic interoperability of product models - Gupta, Ravi Kumar (Strojniški vestnik, 2008)
The paper addresses the problem of exchanging product semantics along with other product information such as shape. Exchanging the semanticsžmeaning associated with shape data enables manipulation of and reasoning with the shape model at higher levels of abstraction. The semantics associated with shape data can convey design intent, inter-relationships between entities in the shape and other data important for downstream applications such as manufacturing. As the product model does not support semantics, its use in other systemsždomains leads to construction of new models. Using a single product model across the product lifecycle is beneficial from the point of view of maintaining integrity of the data and avoiding the effort in creating multiple models. The paper first identifies different types of semantic interoperability problems arising during exchange of product models in product development. These are: different terms referring to same shape, different representations for a shape, meaning of terms are context dependent and mismatch in entities supported in two. We present a one-to-many framework for exchange of product information model, product semantics in particular. This framework is built using the Domain Independent Form Feature (DIFF) modelas the representation of features in the shape model along with an ontology that captures the vocabulary in use in feature models. A reasoning module that can extract multiple construction/views of a feature has also been developed. This reasoning module is used to associate multiple construction paths for the features and associate all applicable meanings fromthe ontology with the DIFF model. Each CAD system can now use the semantics and construction history supported by it to further manipulate the product model. Results of implementation of the use of the above solution in exchanging product semantics with a commercial CAD system will be presented and discussed.
Keywords: izdelki; semnatika; informacije